In Silico Docking Analysis to Identify Therapeutic Benzoic Acid Derivatives for Acute Myeloid Leukaemia - Shruthi P.; Pranesh Kulasehkar; Vrithi Raju (International Journal of Cell Biology and Cellular Functions, 2023)
Background: The study is anchored to initiate subjugation against modern cancer therapy for Acute Myeloid Leukaemia (AML) which involves natural therapeutics as an alternative therapy that would degrade the prospect of adverse side effects along with anti-cancer properties. Objectives: Collate the various characteristics of Giltertinib with natural benzoic acid derivative phytochemicals for a disquisition regarding their similarities and differences in the context of providing adverse side effects. Methods: ADME toxicity studies and molecular docking were administered by using various In silico software such as ADMET Lab 2.0, PyRx docking tool, and BIOVIA studio for visualization. Results: The structural similarity of Giltertinib with the natural phytochemicals holds the correlation of the natural phytochemicals along with various parameters on a comparative scale for further studies. Natural phytochemicals can be used as an alternative form of modern treatment, as the binding energy has shown promise in meeting Giltertinib's limit. Conclusion: The aforementioned findings support the use of compounds of naturally occurring benzoic acid as treatments for AML. According to In silico research, they even have more bioavailability and a lower risk of adverse side effects when compared to Giltertinib in terms of the ADME and toxicity parameters.
Keywords: ADME; AML; In silico; Phytochemicals; giltertinib